(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Food waste is a pressing global issue, and its management within institutional catering facilities is of paramount importance. Institutions such as College, hospitals, and corporate cafeterias generate substantial amounts of food waste, contributing to environmental concerns and economic inefficiencies. This abstract presents a comprehensive study aimed at identifying efficient strategies for handling food waste in institutional catering settings. Objectives: The primary objectives of this study were to Investigate the multifaceted impact of food waste management strategies in institutional catering and propose practical recommendations to enhance food waste management in these settings. Methodology: To achieve these objectives, a quantative -methods approach specifically descriptive research design was employed. Data was collected through online questionnaire through google form from few students who had explored few sets of institutional catering facilities. convenience sampling method was used for the data collection. Sample size was 194.Data were analysed using software spss 23 on the basis of Likert scale-based questionnaire. Results: The results of the one-sample tests indicate a significant difference (p < 0.001) in food waste generation between institutions implementing various food waste reduction strategies, with a mean difference of 2.98 (95% CI: 2.786 to 3.183). Additionally, there’s a significant difference (p < 0.001) in the cost of food waste disposal between institutions employing waste reduction practices and those that do not, with a mean difference of 3.06 (95% CI: 2.868 to 3.256). The adoption of various approaches to cut down on food waste in institutional catering has shown a clear impact on the quantity of food waste generated. This discovery underscores the considerable potential of these strategies in decreasing the volume of food waste generated. Conclusion: Institutional catering can significantly reduce food waste through strategic implementation of waste reduction practices, menu planning, staff training, technology utilization, and customer engagement, resulting in cost savings, environmental benefits, and enhanced compliance and satisfaction.